Formulation And Characterization of Lovastatin Tablets Enteric and Non-enteric Coated with Polymer Blends for Colon-specific Drug Release - Katole, Gayatri; R.D., Wadulkar; M. Bagade, Om; Santosh Karanje, Pallavi; K Chatekar, Vishwajeet; Solanki, Nikunj; Biswa Saikia, Himanta; Vodeti, Rajeshwar (Journal of Neonatal Surgery, 2025)
The study focused on developing a colon-specific drug delivery system for Lovastatin using β-cyclodextrin inclusion complexes and compression-coated tablets. The inclusion complexes were prepared via a kneading method, where Lovastatin was mixed with β-cyclodextrin in a 1:2 molar ratio. Core tablets were formulated using direct compression, incorporating Lovastatin, β-cyclodextrin, and excipients. These cores were subsequently coated with polymer blends of Inulin with either HPMC or Ethyl Cellulose to achieve colon-specific drug release. The swelling behaviour of the polymers was evaluated in an acidic medium, revealing that HPMC exhibited significant swelling, while Ethyl Cellulose formed a film-like layer. The phase solubility study indicated a 1:2 complex formation between Lovastatin and β-cyclodextrin, enhancing drug solubility. XRD and DSC analyses suggested a transition of Lovastatin to an amorphous state within the complex. Drug release studies demonstrated that selected formulations effectively protected the drug in the upper gastrointestinal tract and ensured release in the colon. This research highlights the potential of the developed system for targeted delivery of Lovastatin to the colon, which could improve therapeutic outcomes for conditions like hypercholesterolemia.